4CPS-191 How well do we cover pharmacogenetic recommendations included in the drugs' summaries of product characteristics (spcs)?. (2nd March 2018) - García-González, X; Ortega, C; Ibañez, S; García, MI; Blanco, C; Salvador, S; Sanjurjo, M; López-Fernández, LA
Abstract : Background: Many drugs' Summaries of Product Characteristics (SPCs) incorporate information relating to DNA variants in genes with the potential to alter the drug's efficacy and safety. The European Medicines Agency (EMA) does not issue an official list of these drugs and determinations, which makes implementation and enforcement extremely complicated. PharmGKB annotates drug labels containing pharmacogenetic information and their list can help to address this task. Purpose: To review pharmacogenetic information in the national SPCs of commercialised drugs and assess availability of the suggested genetic tests in our institution. Material and methods: The list of drugs containing pharmacogenetic information in their European SPC according to PharmGKB was obtained from their website in December 2016. SPCs of all drugs included in that list that were commercialised in our country at the time of study were reviewed, and the exact pharmacogenetic information they contained was collected and classified as: testing required, testing recommended/actionable pharmacogenetics or informative pharmacogenetics. We then assessed how many of those tests were available in our institution (in-house or outsourced). Results: According to PharmGKB, 96 drugs contain pharmacogenetic information in their European SPC: 92 of these drugs were commercialised in our country at the time of the study. The pharmacogenetic information included was: 36 (39%) testing required, 23 (25%) testing recommended/actionable and 33 (36%) informative. We determined that 29 (80%) of the required determinations are currently performed in our institution before treatment is initiated: two of them (HLA-B*5701/abacavir and CYP2D6/eliglustat) are offered by the pharmacogenetics laboratory in the pharmacy service. Of the 23 drugs that contain recommended/applicable genetic tests, 16 (70%) refer to a test that is currently available in our pharmacogenetics laboratory (CYP2D6, CYP2C19, DPYD, TPMT and UGT1A1). Of those drugs with informative information, 15 (45%) are covered by these tests, although the number of SPCs naming genes or enzymes with the potential to affect the drug's pk/pd is probably underestimated in the PharmGKB list. Conclusion: Our institution offers genetic determinations for most drugs that include them in their SPC. Required determinations are well covered, but requests remain suboptimal for those recommended/actionable. EMA official guidance should be issued on how to address this issue. No conflict of interest